Complementary and Alternative Medicine for Management of Premature Ejaculation: A Systematic Review. Issue 1 (30th December 2016) - Cooper, Katy; Martyn-St James, Marrissa; Kaltenthaler, Eva; Dickinson, Kath; Cantrell, Anna; Ren, Shijie; Wylie, Kevan; Frodsham, Leila; Hood, Catherine
Abstract: Introduction: Premature ejaculation (PE) is defined as ejaculation within 1 minute (lifelong PE) or 3 minutes (acquired PE), inability to delay ejaculation, and negative personal consequences. Management includes behavioral and pharmacologic approaches. Aim: To systematically review effectiveness, safety, and robustness of evidence for complementary and alternative medicine in managing PE. Methods: Nine databases including Medline were searched through September 2015. Randomized controlled trials evaluating complementary and alternative medicine for PE were included. Main Outcome Measures: Studies were included if they reported on intravaginal ejaculatory latency time (IELT) and/or another validated PE measurement. Adverse effects were summarized. Results: Ten randomized controlled trials were included. Two assessed acupuncture, five assessed Chinese herbal medicine, one assessed Ayurvedic herbal medicine, and two assessed topical "severance secret" cream. Risk of bias was unclear in all studies because of unclear allocation concealment or blinding, and only five studies reported stopwatch-measured IELT. Acupuncture slightly increased IELT over placebo in one study (mean difference [MD] = 0.55 minute, P  = .001). In another study, Ayurvedic herbal medicine slightly increased IELT over placebo (MD = 0.80 minute, P  = .001). Topical severance secret cream increased IELT over placebo in two studies (MD = 8.60 minutes, P < .001), although inclusion criteria were broad (IELT < 3 minutes). Three studies comparing Chinese herbal medicine with selective serotonin reuptake inhibitors (SSRIs) favored SSRIs (MD = 1.01 minutes, P  = .02). However, combination treatment with Chinese medicine plus SSRIs improved IELT over SSRIs alone (two studies; MD = 1.92 minutes, P < .00001) and over Chinese medicine alone (two studies; MD = 2.52 minutes, P < .00001). Adverse effects were not consistently assessed but where reported were generally mild. Conclusion: There is preliminary evidence for the effectiveness of acupuncture, Chinese herbal medicine, Ayurvedic herbal medicine, and topical severance secret cream in improving IELT and other outcomes. However, results are based on clinically heterogeneous studies of unclear quality. There are sparse data on adverse effects or potential for drug interactions. Further well-conducted randomized controlled trials would be valuable.